Organizational capability and process innovation of software project in the Malaysian public sector - Rozaida, M. D.; Mahanum, Daim (Research Publish Journals, 2018)
This study used the partial least square (PLS) and structural equation modeling (SEM) tool to examine factors influencing the process innovation as the competitive advantage in organization. Statistical results confirm that coordination of expertise, communication plan, IT infrastructure flexible and IT infrastructure reach impact on process innovation in software project in the Malaysian public sector. Besides indicating the suitability of the PLS in statistical analysis, the result has also contributed to a better understanding the process innovation in an organization. Findings are useful for IT Managers and practitioners to achieve its competitive advantage through a well-planned organizational capability.